La familia y su influencia en el comportamiento de los niños y niñas internos del albergue infantil “Padre Julio Villarroel Ocaña”, de la ciudad de Loja. Periodo enero a julio del 2014 - Vicente Jiménez, Alexandra Isabel (2014)
The present research, YSU Family Influence on Behavior of Children and Child Internal Girls Hostel "Father Julio Ocaña Villarroel" City of Loja. Period January to July 2014, "is performed by the type of descriptive research. Techniques were used as clinical psychological history, surveys and observation sheets; this served to get the results of the problem; was taken as 15 people total sample corresponding to 10 children / as & 5 teachers. Well as the overall objective was proposed, inquire; how the family influences the behavior of children and child domestic girls hostel "Father Julio Ocaña Villarroel," and as specific, determine the type of family and parenting style have children and finally establish the type of behavior that currently hold. After reviewing all this came to the conclusion that children who are inmates; have had a type of single-parent family; that family that consists of a single member of the parental couple, so the parenting style that is permissive have had which has not been favorable; Speaking of families or parents who do not set limits for their children ymuestran little interest in them and their behavior, just as it has been concluded that the type of behavior that is currently maintained aggressive. Consecutively some recommendations raised with the authorities, the technical staff, and faculty of the institution, to take into account these drawbacks, for seeking to improve their intervention, a multidisciplinary working and updating their knowledge, so they can provide a safe environment and emotional support that children need and that they had in their homes.